Design and fabrication of SWNT-FET based biosensor - Mohd Syamsul Nasyriq, Samsol Baharin
Nanotubes have generated intense research activities from scientists of various disciplines because they represent a new class of materials for the study of one-dimensional physics. Single-walled carbon nanotubes (SWNTs) have many other magnificent properties and it has impressive properties in three aspects, mechanical, electrical and biological due to ability of single-walled carbon nanotubes (SWNTs) to exhibit self-assemble monolayer (SAM). The main objective of this project is to design and fabricate carbon nanotube based biosensor for future application medical diagnostics. The electrical transport of semiconducting single-walled carbon nanotubes with the diameter of ~1.5 nm and length of 2 μm to 6 μm for its applications as biomolecules detection was investigated. Single-walled carbon nanotubes field effect transistors (SWNT-FET) were fabricated in house using three masks designed. Initially backgated field effect transistor (FET) was formed and followed with the growth of oxide as insulation layer. Multilayer metal of platinum,Pt and gold,Au were grown on top of oxide layer and finalized with the integration of single-walled carbon nanotubes (SWNTs). The oxide thickness achieved is ~18nm and multilayer metal of platinum,Pt and gold,Au thickness is ~10nm and ~90nm respectively. The integration of single-walled carbon nanotubes (SWNTs) with field effect transistor (FET) was performed using AC dielectrophoresis nanomanipulation technique resulting promising results of integration proven via Scanning Electron Microscope (SEM). Fabricated device resulting conductance of G ~ 0.03 x 4e2/h and hole mobility of μp ~ 3060 cm2/V.s in saturation mode. This device also shows resemblances with conventional p-type metal-oxide-semiconductor FETs (MOSFETs) through IDS-VDS curve and appears to be gate voltage dependence through conductance-gate voltage curve. Thus, these results prove that fabricated device functioned as p-type metal-oxide-semiconductor FETs (MOSFETs) and can be used for the application of biomolecules detection such as protein by monitoring the device changes of IDS-VDS characteristics.